Patent Protection, Market Uncertainty, and R&D Investment - Czarnitzki, Dirk; Toole, Andrew A. (The Review of Economics and Statistics, 2011)
The main reason governments grant patent protection is to spur innovation. However, the size of the R&D stimulus from patent protection is far from clear because it depends on how effective patents are as a mechanism for appropriating returns. Drawing on real options investment theory, this paper highlights one mechanism through which patents may improve appropriability and stimulate R&D investment: patents reduce the effect of market uncertainty on the firm’s investment decision. We find that firm-level R&D investment falls in response to higher levels of uncertainty, but that patent protection partially mitigates the influence of uncertainty.